The impact of corruption control on ESG performance: the moderating role of board independence in the European Union - Samara, Husni; Abdul Latiff, Ahmed Razman; Har Loke, Chew (Taylor and Francis, 2026)
This study examines the impact of board independence on the relationship between control of corruption and sustainability in the European Union. Using a balanced panel of 4749 firm-year observations across European Union member states from 2014 to 2023, we draw on Refinitiv Eikon data and apply high-dimensional fixed effect (HDFE), multilevel mixed-effects models (Xtmixed) estimations to address unobserved heterogeneity, dynamic persistence, and endogeneity concerns. The results in dicate that control of corruption positively affects firms’ ESG performance, and this relationship remains stable across alternative model specifications and estimation techniques. Moreover, the analysis reveals that board independence plays a dual role: while it exerts a positive direct effect on ESG performance, it weakens the marginal impact of control of corruption. This suggests that strong internal monitoring mechanisms may partially substitute for external institutional controls. This study provides evidence of how board characteristics (BIND) interact with institutional control corruption to shape sustainability outcomes. It focuses on the importance of ESG performance and demonstrates that control of corruption enhances the ESG performance in large-listed firms within the European Union, while board independence (BIND) plays a complementary governance role. The results provide valuable insights for strategic decision-makers, especially senior management and corporate executives, to enhance their knowledge regarding ESG performance, aiming to ensure corporate sustainability growth. Policymakers and regulators may use these insights to design initiatives and governance guidelines that encourage transparency, accountability, and responsible corporate behavior, thereby supporting broader sustainability objectives and efforts to address corruption-related challenges.